2021
DOI: 10.3390/ma14040891
|View full text |Cite
|
Sign up to set email alerts
|

Research on Carbide Characteristics and Their Influence on the Properties of Welding Joints for 2.25Cr1Mo0.25V Steel

Abstract: The carbide characteristics of 2.25Cr1Mo0.25V steel have an extremely important influence on the mechanical properties of welding joints. In addition, hydrogen resistance behavior is crucial for steel applied in hydrogenation reactors. The carbide morphology was observed by scanning electron microscopy (SEM) and the carbide microstructure was characterized by transmission electron microscopy (TEM). Tensile and impact tests were carried out and the influence of carbides on properties was studied. A hydrogen dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…The results showed that there was a significant difference between the base metal and weld metal of the weldment, including both the microstructure and tensile strength. A more recent work performed by Li et al [ 13 ] also investigated the tensile and impact responses of 2.25Cr1Mo0.25V steel parent metal and weld at room temperature. Their results showed that the weld metal exhibited higher strength but lower toughness than the parent metal, which may be due to the presence of more carbides and inclusions in weld.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that there was a significant difference between the base metal and weld metal of the weldment, including both the microstructure and tensile strength. A more recent work performed by Li et al [ 13 ] also investigated the tensile and impact responses of 2.25Cr1Mo0.25V steel parent metal and weld at room temperature. Their results showed that the weld metal exhibited higher strength but lower toughness than the parent metal, which may be due to the presence of more carbides and inclusions in weld.…”
Section: Introductionmentioning
confidence: 99%